We're going on a bear hunt - Rosen, Michael; Oxenbury, Helen (London : Walker Books, 1997)
Brave bear hunters go through grass, a river, mud, and other obstacles before the inevitable encounter with the bear forces a headlong retreat.
On board pages.
Keywords: Children's stories